2013
DOI: 10.1063/1.4818674
|View full text |Cite
|
Sign up to set email alerts
|

Crystal domain growth driven by nanometric phase separation in perfect surface crystallization

Abstract: Phase separation often makes glass structure inhomogeneous. Nevertheless, a uniform texture consisting of single-crystal domains has been found by crystallization in nonstoichiometric glass, i.e., perfect surface-crystallization (PSC). Although the PSC is probably caused by evolution of SiO2-rich amorphous nanoparasites on the domain, its mechanism has not been understood yet. In this study, we examined an early-stage of PSC in a strontium-titanosilicate glass by means of nanoscopic observations. It was demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…21. In contrast to the transparent glass ceramics previously achieved by annealing at lower temperatures for shorter time periods18192021, the resulting samples were rather opaque as shown in Figure 1a) and b). This is in agreement with the bluish white color observed after annealing at 880°C18.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…21. In contrast to the transparent glass ceramics previously achieved by annealing at lower temperatures for shorter time periods18192021, the resulting samples were rather opaque as shown in Figure 1a) and b). This is in agreement with the bluish white color observed after annealing at 880°C18.…”
Section: Resultsmentioning
confidence: 78%
“…So far EBSD is the only method with which oriented nucleation may be detected with certainty and EBSD has not been applied to the systems for which the growth model A is proposed to be valid. ii) High quality TEM results of glass A featuring a single crystal domain at the surface as well as the growth front only show uncrystallized glass, crystalline fresnoite and residual glass19. An area where two phase separated liquids coexist was not proved.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…1(d)]. In the previous studies2532, the nanometric parasites are due to the nanometric phase-separation into stoichiometric fresnoite-component and residual SiO 2 component, which finally transform to the crystal-domain and nanometric parasites, respectively. The assessment indicates that the sample obtained in this study is compatible with the PSC-GCs reported so far2426, and consequently it is considered that the obtained sample acquires the PSC features of i) to iii).…”
Section: Resultsmentioning
confidence: 97%